Anti-icing properties of nonionic/hydrophilic concentrated polymer brushes and mechanistic insights via their swollen-state analysis - Ken Tamamoto; Yuji Kinose; Hikaru Okubo; Ken Nakano; Yoshinobu Tsujii (Communications Materials)
Abstract Anti-icing surfaces are important to prevent snow and ice accumulation, which can pose significant risks. Here, we analyze the anti-icing performance of concentrated polymer brushes (CPBs) consisting of a versatile nonionic/hydrophilic monomer and discuss the low-temperature properties of the CPB-retaining water. The anti-icing functionality is evaluated by measuring the ice adhesion strength as a function of the temperature and the structural parameters (e.g., density and length) of the polymer brushes. We demonstrate that only the CPB region (σ* ≥ 0.15) exhibits both high anti-icing functionality and excellent durability. Furthermore, the thickening of the CPBs is key to achieving a detailed characterization of the water present in the CPBs at low temperatures using in situ microscopic Fourier-transform infrared spectroscopy and differential scanning calorimetry. These results suggest that the water effectively remaining via quasi-equilibrium partial deswelling formed a lubricating layer, contributing to high anti-icing functionality and durability.